Saving Hydrogen Fuel Consumption and Operating at High Efficiency of Fuel Cell in Hybrid System to Power UAV - Baba Omar; Al Savvaris; Rahil O; Abdulhadi; Muhammad Khairul Afdhol; Muhammad Hasibuan (Universitas Islam Riau (UIR) Press, 2021)
The present fuel cell technology is under considerations as a potential power source for Unmanned Aerial Vehicles. Fuel cells are an electrochemical power plant that takes hydrogen and oxygen as inputs and produces electricity, water and heat as outputs. Most of the global hydrogen production is from non-renewable fossil fuels. Therefore, this paper investigates how to save hydrogen fuel consumption and operate at high efficiency in the fuel cell/battery hybrid system to power a small Aircraft. We achieved that by working on the power management of the fuel cell/battery hybrid propulsion system for small UAV by using the fuzzy logic controller and charging up the batteries. The hybrid propulsion system consists of a 1.2kW PEM fuel cell, three 12V batteries, DC/DC converters, and an electric engine. The fuzzy logic controls the batteries' output powers through the bidirectional DC/DC converter. It will help maintain the fuel cell operates at an optimal point with high efficiency as the main power supply for different flight phases to achieve the desired power.